Phytochemical screening, antioxidant and antibacterial activity of crude extracts from leaves of Cordia myxa tree grown in Iraq. (Journal of the College of Basic Education, 2025)
Cordia myxa, Lasura tree, is a medium-sized deciduous tree from the borage family (Boraginaceae( .It is one of the traditional medicinal plants, that has been used for more than decades in Iraq to treat many diseases. Thus, the present study was conducted to analyze the phytochemical constituents and antioxidant/antibacterial properties of this plant's aqueous and ethanolic leaf extracts. Results show that aqueous and ethanolic leaf extracts of Cordia myxa were revealed to have substantial phenol content as 89.24 and 67.55 mg gallic acid/g of dried extracts respectively, while flavonoid contant is 3.12 and 1.42 mg quercetin/g of dried aqueous and ethanolic extract respectively. The highest percentage of DPPH radical inhibition (86.45%), was achieved by ethanol extract at the concentration of 1 mg/ml with good antibacterial activity against Salmonella typhi, Pseudomonas aeruginosa, Shigella sonnei, and Klebsiella pneumonia with mean diameter of inhibition zone (12, 13, 14, and 16 mm respectively). Therefore, it turns out that it could be a strong candidate for developing a natural medicine against microbial infections.